Finite element analysis and experimental study on metal joining by mechanical crimping. (23rd December 2014) - Kalyan Kumar, R.; Suresh Babu, A.
This paper aims to provide an innovative joining method of mechanical crimping by plastic deformation of materials. Crimping is considered as a mechanical joining method of getting a permanent joint which involves plastic deformation by compressing material of one part over another part. The crimping operation generally involves a time consuming trial and error approach to get an optimum joint. It leads to more material wastages and rely on experience in joining metals. This present study investigates the crimping operation of an aluminium plunger and a steel push rod as used in a typical hydraulic clutch master cylinder assembly. By using finite element analysis software ANSYS, the crimping operation was simulated and various crimping parameters were evaluated. It was possible to determine the optimum crimping parameters numerically. The numerically evaluated and optimised parameters were used to obtain a physical crimp joint with a bench type simple crimping machine. The numerical and experimental results were investigated and found that the results are in good agreement. This work also includes the analysis of joint performance by conducting a pull-out load test both numerically and experimentally.